Good Knowledge of COVID-19 Increased Preventive Behavior on Last Year Undergraduate Medical Students at University of Jember, East Java, Indonesia - Raghda Gita Safitri; Ancah Caesarina Novi Marchianti; Laksmi Indreswari (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Indonesia is in first place in ASEAN regarding the high number of confirmed cases and deaths of Covid-19 on November 9, 2020. This can be caused by a lack of preventive behavior related to Covid-19, one of which is influenced by knowledge. The purpose of this study was to determine the relationship between knowledge level of Covid-19 and Covid-19 preventive behavior in last year undergraduate medical students at University of Jember.Subjects and Method: A cross sectional study was conducted online through a questionnaire that will be distributed using Google form in May 2021. A total of 121 last year undergraduate medical students at University of Jember were enrolled using a total sampling technique. The dependent variable is level of knowledge related to Covid-19 and the independent variable is Covid-19 preventive behavior. The data obtained through Google form will be analyzed using the SPSS version 26.0 application and using the Spearman Rho Correlation method. Results: Based on univariate analytic, 97.5% students have a good knowledge and 90.9% students perform high preventive behavior of Covid-19. Bivariate analytic by testing correlation ¬between one’s knowledge of Covid-19 and the preventive behavior obtained p <0.001 correlation coefficient of 0.504.Conclusion: The good knowledge of Covid-19 increased preventive behavior on last year undergraduate medical students at University of Jember.Keywords: Physical distancing, Covid-19, online questionnaire.Correspondence: Ancah Caesarina Novi Marchianti. Faculty of Medicine, University of Jember. Jl. Kalimantan Tegalboto 37, Jember, East Java, Indonesia. Email: ancah@unej.ac.id. Mobile Phone:+62331-337877.Journal of Health Promotion and Behavior (2021), 06(02): 97-103https://doi.org/10.26911/thejhpb.2021.06.02.02